Α1-Antitrypsin alleviates inflammation and oxidative stress by suppressing autophagy in asthma. (May 2021) - Huang, Chang-Yu; Hu, Rui-Cheng; Li, Jie; Chen, Bin-Bin; Dai, Ai-Guo
Highlights: Activation of autophagy compromised the protective effect s of A1AT in asthma model. A1AT could alleviate the inflammation and oxidative stress in asthma. A1AT alleviated the inflammation and oxidative stress via inhibiting autophagy. Abstract: Background: Asthma is considered an incurable disease, although many advances have been made in asthma treatments in recent years. Therefore, elucidating the pathological mechanisms and seeking novel and effective therapeutic strategies for asthma are urgently needed. Methods: Airway resistance was measured by whole-body plethysmography. H&E staining was used to observe the morphological changes in the lung. Oxidative stress was assessed by measuring the levels of MDA, CAT and SOD. Gene expression was analysed by western blotting and RT-qPCR. ELISA was used to analyse the concentrations of IL-4, IL-5 and IFN-γ. Results: In the present study, we successfully established in vivo and in vitro asthma models. OVA administration led to elevated lung resistance, cell counts in BALF, and cytokine secretion, impaired airway structure and enhanced oxidative stress and autophagy in a mouse model of asthma, while IL-13 induced inflammation, oxidative stress and autophagy in BEAS-2B cells. A1AT reduced lung resistance and cell counts in BALF and suppressed inflammation, oxidative stress and autophagy in a mouse model of asthma and IL-13-induced BEAS-2B cells. Mechanistic investigations revealed that autophagy activation compromised the protective effect of A1AT on IL-13-induced BEAS-2B cells. Further mechanistic studies revealed that A1AT alleviated inflammation and oxidative stress by inhibiting autophagy in the context of asthma. Conclusion: We demonstrated that A1AT could alleviate inflammation and oxidative stress by suppressing autophagy in the context of asthma and thus ameliorate asthma. Our study revealed novel pathological mechanisms and provided novel potential therapeutic targets for asthma treatment.